Renal tissue pro-inflammatory gene expression is reduced by erythropoietin in rats subjected to hemorrhagic shock - Mina Ranjbaran; Mehri Kadkhodaee; Behjat Seifi (Journal of Nephropathology, 2017)
Background: Hemorrhagic shock (HS) is a condition produced by considerable loss of intravascular volume, which may eventually lead to organ damage and death. Objectives: In the present study, the potential implication of the kidney tissue tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-10 (IL-10) were evaluated in the protective effects of erythropoietin (EPO) during HS. Materials and Methods: Male Wistar rats were randomized into three experimental groups; Sham, HS (hemorrhagic shock and resuscitation), and EPO (erythropoietin). HS was induced by 50% blood volume hemorrhage over 30 minutes. After 2 hours, resuscitation was performed within 30 minutes. In the EPO group, EPO (300 IU/kg, i.v.) was administered 10 minutes before HS induction. Urine was collected to determine urinary N-acetyl-β-D-glucosaminidase (NAG) activity level. The kidney cytokines (TNF-α, IL-6 and IL-10) mRNA expressions were measured by real-time polymerase chain reaction (PCR). Results: HS rats showed significant increase in urinary NAG activity compared to the sham group. EPO significantly attenuated the rises in urinary NAG activity compared to the HS group. In the HS animals, renal TNF-α and IL-6 mRNA expressions increased whereas no difference was observed in IL-10 mRNA expression between the HS and sham groups. EPO was able to decrease renal TNF-α and IL-6 production and increase IL-10 mRNA expression. Conclusions: In this study, we demonstrated that EPO attenuates kidney damage in rats subjected to HS. The beneficial effects of EPO may be at least partly mediated by modifications in the inflammatory cascade.